The Effect of Social Commerce Information Sharing on Hotel Booking Intention in China - Li, Yanbo (2019)
Social commerce – “social media + e-commerce” – is a new market place for both consumers and marketers. Also considering the consumers’ uncertainty brought by intangible service domain, therefore, this paper explores the relationship between social commerce information sharing and hotel booking intention. This study uses Mehrabian and Russell’s “Stimulus- Organism-Response” (SOR) model and hotel brand loyalty building, hedonic value, trust transfer, herding behaviour are chosen to be “Organisms” in this framework to investigate the moderating effect. It carries out an analysis of primary data obtained from users of a Chinese social commerce site operating in the field of hotel booking (Mafengwo, similar to TripAdvisor) and it uses that analysis to draw practical conclusions and advices.